2011
DOI: 10.1063/1.3622671
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of cubic ZrO2 nanoparticles on ionic conductivity of polyethylene oxide-based composite

Abstract: A solvent free solid composite polymer electrolyte (SCPE) film consisting of high molecular mass polyethylene oxide (PEO) with sodium perchlorate (NaClO 4 ) as electrolytic salt and cubic zirconium oxide (ZrO 2 ) nanoparticles as the filler has been prepared by solution casting technique to influence the transport properties. X-ray diffraction and Fourier transform infrared spectroscopy confirm the formation of the SCPE film, whereas atomic force microscopy reveals the presence of a network of interconnected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The importance of polymer crystallinity in the study of CPEs cannot be overrated. Crystallinity is affected by temperature, amount of lithium salt and nanoparticle changes [26,62,63,64,67,68]. Crystallinity underlies the performance of CPEs such as conductivity and mechanical strength.…”
Section: Nanoparticle Additives Affect the Polymer Electrolyte Strmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of polymer crystallinity in the study of CPEs cannot be overrated. Crystallinity is affected by temperature, amount of lithium salt and nanoparticle changes [26,62,63,64,67,68]. Crystallinity underlies the performance of CPEs such as conductivity and mechanical strength.…”
Section: Nanoparticle Additives Affect the Polymer Electrolyte Strmentioning
confidence: 99%
“…The polymer chain conformation influences the dynamics of the lithium ions coordinated with the polymer backbones [ 69 ] because Li + ions exhibit different binding energies with the different conformers [ 70 ]. The polymer chain conformation can change due to nanoparticle addition as shown by Raman [ 62 ] and FTIR spectroscopy [ 67 , 71 , 72 ]. In the 700–1600 cm −1 Raman spectra of a PEO-sodium montmorillonite system, there are four characteristic regions corresponding to four types of vibration bands: CH 2 rocking vibrations, C–O–C stretching vibrations, CH 2 twisting vibrations and CH 2 bending vibrations [ 62 ].…”
Section: Nanoparticle Additives Affect the Polymer Electrolyte Strmentioning
confidence: 99%
“…In the case of gel polymer electrolytes, an enhanced ion conductivity in comparison with the separator without ceramic fillers was reported [51]. This finding was assigned to the interaction of the polar surface groups of the gel electrolyte and the ceramic particles, which created additional conduction pathways for the ion transport.…”
Section: Definition Properties Materialsmentioning
confidence: 70%
“…More than a decade ago, Prosini et al [59] reported the development of a composite separator for lithium-ion batteries that utilized Al 2 O 3 , MgO 2 , and LiAlO 2 ceramic particles as fillers for a PVDF-HFP polymer matrix. Among them, Al 2 O 3 became the most popular filler [50,54,56,59,62,63], but TiO 2 [64], CaCO 3 [58], SiO 2 [14,50,54,63,65] and ZrO 2 [50,51,63] have also been used. In general, besides the mentioned oxides and carbonates, also nitrides or carbides of Si, Al, Zr, Sn, Ce or Y have been suggested [50], such as SiC [63].…”
Section: Definition Properties Materialsmentioning
confidence: 99%
See 1 more Smart Citation